erythro-2-Piperidinyl-1,2-diphenylethanol - Ocak, N; Kazak, C; Öztürk, S; Zerrin, C; Arsu, N; Fun, HK; Erdönmez, A (INT UNION CRYSTALLOGRAPHY, 2002)
The molecule of the title compound, C19H23NO, contains two phenyl rings and a piperidinyl ring. The dihedral angle between the phenyl rings is 40.99 (5)degrees. The piperidine ring has a chair conformation. There is an intramolecular O-H...N hydrogen bond.
Keywords: DRUG; Crystallography